Is it a Choice? Examining Neoliberal Influences in Three Ontario Education Reforms - Di Giovanni, Adamo; Parker, Lana (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2024)
In this article, we draw on various critical perspectives to theorize neoliberal choice and examine how it has been deployed to market new educational reforms in Ontario. We begin by offering a contemporary framing of neoliberalism that looks at its core elements as well as its chameleon-like tendencies to draw on neoconservative elements as needed. We also furnish critiques of neoliberalism by engaging Adams et al.’s (2019) description of neoliberal “choice” as one component of a larger psychological exercise in support of capitalism. We then examine how the language of choice has been used to position three recent Ontario education reforms: (a) mandatory e-learning; (b) growth of international students; and (c) the revision of curricula according to economic ends. Finally, we argue that the implementation of these reforms ironically has produced less choice for stakeholders through austerity and standardization.